2013
DOI: 10.1038/ncomms3164
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of poly(ADP-ribose) bound to PARG reveals inherent balance between exo- and endo-glycohydrolase activities

Abstract: Poly-ADP-ribosylation is a post-translational modification that regulates processes involved in genome stability. Breakdown of the poly(ADP-ribose) (PAR) polymer is catalysed by poly(ADP-ribose) glycohydrolase (PARG), whose endo-glycohydrolase activity generates PAR fragments. Here we present the crystal structure of PARG incorporating the PAR substrate. The two terminal ADP-ribose units of the polymeric substrate are bound in exo-mode. Biochemical and modelling studies reveal that PARG acts predominantly as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
174
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(181 citation statements)
references
References 30 publications
(44 reference statements)
6
174
0
1
Order By: Relevance
“…Furthermore, this PARG-PAR structure also revealed that PARGs preferably bind PAR at the chain termini and primarily act as exo-glycohydrolases (whereby PARG sequentially degrades terminal ADP-ribose units). While binding along the PAR chain and endo-glycohydrolytic cleavage of PAR is structurally possible, it appears to be less efficient (Barkauskaite et al, 2013a;Braun et al, 1994;Lambrecht et al, 2015;Tucker et al, 2012). Such PARG endo-glycohydrolase activity may become significant in vivo at high PAR/ PARG ratios (for example, in the case of an extreme cellular insult), thus releasing free PAR fragments to mediate apoptotic signaling (Andrabi et al, 2006;Barkauskaite et al, 2013a).…”
Section: Pargmentioning
confidence: 92%
See 3 more Smart Citations
“…Furthermore, this PARG-PAR structure also revealed that PARGs preferably bind PAR at the chain termini and primarily act as exo-glycohydrolases (whereby PARG sequentially degrades terminal ADP-ribose units). While binding along the PAR chain and endo-glycohydrolytic cleavage of PAR is structurally possible, it appears to be less efficient (Barkauskaite et al, 2013a;Braun et al, 1994;Lambrecht et al, 2015;Tucker et al, 2012). Such PARG endo-glycohydrolase activity may become significant in vivo at high PAR/ PARG ratios (for example, in the case of an extreme cellular insult), thus releasing free PAR fragments to mediate apoptotic signaling (Andrabi et al, 2006;Barkauskaite et al, 2013a).…”
Section: Pargmentioning
confidence: 92%
“…The accessory domain (which is part of the PARG catalytic region) has only limited interaction with PAR, but it structurally supports the PARG catalytic loop and may have an important role in regulation of PARG catalytic activity (Barkauskaite et al, 2013a). Furthermore, this PARG-PAR structure also revealed that PARGs preferably bind PAR at the chain termini and primarily act as exo-glycohydrolases (whereby PARG sequentially degrades terminal ADP-ribose units).…”
Section: Pargmentioning
confidence: 95%
See 2 more Smart Citations
“…It utilizes NAD (NAD ϩ ) to form PAR at the DNA lesions or breaks, thereby posttranslationally modifying itself and other proteins of interest. Importantly, PAR formation is highly dynamic, because shortly after being synthesized, it is rapidly hydrolyzed by PARP's catabolic counterparts, PAR glycohydrolase (PARG) and ADP-ribosylhydrolase 3 (ARH3) (5)(6)(7)(8). Neither enzyme is able to remove the last ADP-ribose moiety from acceptor proteins; macrodomain-containing proteins, such as MacroD1 and MacroD2, fulfill this task, leaving behind an unmodified amino acid that is readily available for the next round of poly-(ADP-ribosyl)ation (PARylation) (9,10).…”
mentioning
confidence: 99%